Pengaruh Pengungkapan Sukarela, Penghindaran Pajak dan Corporate Governance terhadap Biaya Hutang - Baiq Fitri Arianti (SAFE-Network, 2022)
This research aims to test and provide empirical evidence of the effect of voluntary disclosure, tax avoidance and corporate governance on the cost of debt by consumer goods manufacturing sector companies listed on the Indonesia Stock Exchange in the period 2013 - 2017. The population in this study is all sector manufacturing companies goods and consumption listed on the Indonesia Stock Exchange for the period 2013-2017. The sample method used in this study was purposive sampling method with a total of 12 companies in the consumer goods industry sector during 5 years of observation. Data analysis used is multiple linear regressions with the help of SPSS 22.0 software program. The results of this study indicate that voluntary disclosure does not have a significant effect on the cost of debt. Tax avoidance has an effect on the cost of debt and corporate govenance has an effect on debt costs. While simultaneously it also shows that voluntary disclosure, tax avoidance and corpoate governance affect the cost of debt.